Assessment the effects of insulin on adiponectin, nitric oxide, myeloperoxidase and lipid profile in type 1 diabetic patients - Jehan A. Mohammad; Zainab H. Fathi; Thikra Ali Allwash (Pensoft Publishers, 2021)
Type 1 diabetes (T1DM) is well recognized risk factor cardiovascular disease (CVD). Insulin therapy is recommended for all patients with type 1 diabetes. Previous findings showed that diabetes impairs endothelial function and increased glucose level reduces nitric oxide (NO) output and increases myeloperoxidase (MPO) activity. However, adiponectin (APN) decreases serum glucose levels. The current study evaluated effects of insulin therapy on circulating levels of oxidative stress and CVD biomarkers like NO, APN, MPO, AIP and lipid profile in type 1 diabetic patients. Fifty patients with T1DM and 18 healthy people were enrolled in this study. The recruited people with T1DM were classified into two groups: 22 newly diagnosed (untreated) type 1 diabetic patients and 28 insulin treated patients. In all groups, circulating NO, APN, MPO, AIP and lipids levels were measured. Compared to control, untreated diabetes revealed a significant increase in the serum levels of APN, MPO, TG, VLDL, TC, LDL and AIP, with a marked reduction in NO and HDL levels. However, insulin therapy significantly lowered MPO, TC and LDL, with no significant changes in the other biochemical parameters. As expected, oxidative stress and CVD-associated markers were significantly increased in untreated diabetes. Insulin therapy exhibited a relatively positive effect on oxidative stress and CVD biomarkers. Accordingly, insulin plus antioxidant supplementation required to normalize these parameters.